Aflatoxin Susceptible Food Consumption Frequency, Prevalence, and Levels in Household Foodstuffs in Southwestern Uganda - Biryomumaisho Justus Murokore; Agnes Nandutu Masawi; Alex Paul Wacoo; Raphael Wangalwa; Clement Olusoji Ajayi; Peter Vuzi California (Journal of Food Quality)
Contamination of household foodstuffs by aflatoxins has been associated with many illnesses, especially hepatocellular cancer and malnutrition. Aflatoxins are toxins produced by fungi, especially Aspergillus flavus and Aspergillus parasiticus, usually found in food. Literature concerning the S.W. Ugandan foods that are the main aflatoxicosis route and therefore need most aflatoxin preventive measure is scanty. The current study determined the aflatoxin-susceptible food consumption frequency, prevalence, and levels of aflatoxins in selected foodstuffs in households in S.W. Uganda to establish the main food route of aflatoxicosis. Following a food frequency questionnaire, flour samples of common foodstuffs, namely, groundnuts, maize, millet, and sorghum, were randomly picked from seven districts of Southwest Uganda and analyzed for the presence and levels of aflatoxins using competitive ELISA. On average, maize and groundnut were found to be the most frequently consumed foods (seven times a week) by every family. Groundnuts had the highest mean aflatoxin level (96.5 ± 13.37 μg/kg), ranging from 6.2 to 297.3 μg/kg. Over 90% of the groundnut samples had mean aflatoxin levels greater than 10 μg/kg, the East African regulatory limit. Maize flour had a mean aflatoxin level of 34.1 ± 14.1 μg/kg, with one sample registering 336.5 μg/kg. This study found that groundnuts were the main food-route for aflatoxicosis followed by maize flour. In addition, the study re-affirmed the high prevalence and levels of aflatoxins in common food stuff in households in S.W. Uganda reported by previous studies. This study recommends further studies to elucidate its association with the observed recent increase in diseases like hepatocellular cancer and malnutrition in the region.